New Pathological Lesions Developed in Pigs by a “Non-virulent” Strain of Glaesserella parasuis - Dazzi, Cláudia Cerutti; Guizzo, João Antônio; Prigol, Simone Ramos; Kreutz, Luiz Carlos; Driemeier, David; Chaudhuri, Somshukla; Schryvers, Anthony Bernard; Frandoloso, Rafael (Frontiers in Veterinary Science, 2020)
Glaesserella parasuis is a Gram-negative bacterium that causes Glässer’s disease, a common pathology found in young pigs characterized by polyarthritis, polyserositis and meningitis. The bacterium has 15 known serovars that have been classified by virulence. Serovars 1, 4, 5 and 12 are considered highly virulent and used in most studies. Serovars 3, 6, 7, 9 and 11 are considered avirulent. Recent reports that serovar 7 is an emerging problem in the pig industry indicate that the association of virulence and serovar may not always be reliable. This led us to infect colostrum-deprived piglets with the reference serovar 7 strain (SV7 strain 174) that had been passaged through pigs and characterize the clinical and pathological signs. We observed that SV7 strain 174 caused clinical signs consistent with Glässer’s disease in all infected piglets that succumbed to infection for up to day 5 post-infection. Macroscopic and microscopic lesions were consistent with those found in piglets infected with conventional virulent serovars. In addition, we describe novel microscopic lesions associated with Glässer’s disease such as endophthalmitis and thymic depletion. Thus, our findings indicate that SV7 strain 174 causes classical signs of Glässer’s disease in colostrum-deprived piglets and some caution should be used in employing vaccine strategies based on association between capsular serovar and virulence.